Biomedical authors' awareness of publication ethics: an international survey. Issue 11 (25th November 2018) - Schroter, Sara; Roberts, Jason; Loder, Elizabeth; Penzien, Donald B; Mahadeo, Sarah; Houle, Timothy T
Abstract : Objective: The extent to which biomedical authors have received training in publication ethics, and their attitudes and opinions about the ethical aspects of specific behaviours, have been understudied. We sought to characterise the knowledge and attitudes of biomedical authors about common issues in publication ethics. Design: Cross-sectional online survey. Setting and participants: Corresponding authors of research submissions to 20 journals. Main outcome measure(s): Perceived level of unethical behaviour (rated 0 to 10) presented in five vignettes containing key variables that were experimentally manipulated on entry to the survey and perceived level of knowledge of seven ethical topics related to publishing (prior publication, author omission, self-plagiarism, honorary authorship, conflicts of interest, image manipulation and plagiarism). Results: 4043/10 582 (38%) researchers responded. Respondents worked in 100 countries and reported varying levels of publishing experience. 67% (n=2700) had received some publication ethics training from a mentor, 41% (n=1677) a partial course, 28% (n=1130) a full course and 55% (n=2206) an online course; only a small proportion rated training received as excellent. There was a full range (0 to 10 points) in ratings of the extent of unethical behaviour within each vignette, illustrating a broad range of opinion about the ethical acceptability of the behaviours evaluated, but these opinions were little altered by the context in which it occurred. Participants reported substantial variability in their perceived knowledge of seven publication ethics topics; one-third perceived their knowledge to be less than 'some knowledge' for the sum of the seven ethical topics and only 9% perceived 'substantial knowledge' of all topics. Conclusions: We found a large degree of variability in espoused training and perceived knowledge, and variability in views about how ethical or unethical scenarios were. Ethical standards need to be better articulated and taught to improve consistency of training across institutions and countries.